Validation of the questionnaire OLC (Organizational Learning Culture) in ecuadorian organizations - Ramos, Valentina (2020)
The Organizational Learning Culture Questionnaire (OCL) was developed at the University of Coimbra (Portugal) to measure the culture in organizational environments. The goal of this study is to validate the OLC questionnaire in Ecuadorian organizations, for its application in researches about learning culture. Thus, the first version of the 30-question questionnaire was used and applied to a heterogeneous sample of 193 workers from various organizations (6: 1 ratio). The OLC questionnaire was subject to content validation, making an exploratory factor analysis (15 items, 2 factors, variance=58.6%) and a confirmatory analysis with good adjustment measures (PCFI=.824; RMSEA= 049; CFI=.972). To assess the reliability of the instrument, Cronbach's alpha was used (aexternal adaptation=.889 y ainternal integration=.873). These results demonstrate that the OLC Ecuador questionnaire is valid for the analyzed context. © 2020 AIDEP. All rights reserved.